ENFORCEMENT OF CRIMINAL LAW ON PORNOGRAPHY IN INDONESIA FROM THE PERSPECTIVE OF NATIONAL CRIMINAL LAW REFORM - Mey Sri Yanti W; Iwan Darmawan; Alfies Sihombing (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The development of information and communication technology has brought significant changes to the patterns of production, distribution, and consumption of digital content in Indonesia, including the increased spread of pornographic content thru cyberspace. This phenomenon poses serious challenges in the enforcement of criminal law due to the complex, anonymous, and transnational nature of digital crimes. This research aims to analyze the regulation of pornography offenses in Indonesia, law enforcement from the perspective of national criminal law reform, and the effectiveness of law enforcement in addressing digital pornography. The research method used is normative legal research with a legislative approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are analyzed qualitatively thru descriptive methods. The research results show that pornography offenses in Indonesia are regulated by Law Number 44 of 2008 on Pornography, Law Number 1 of 2023 on the Criminal Code, and the Electronic Information and Transactions Law. However, the diversity of these regulations still creates the potential for normative disharmony, overlapping regulations, and multiple interpretations of the definitions and scope of prohibited acts. Law enforcement against pornography crimes shows a shift from a repressive approach to a preventive and educational approach in line with the direction of national criminal law reform. Nevertheless, its implementation still faces obstacles from the aspects of legal substance, legal structure, and the legal culture of society. The effectiveness of law enforcement against digital pornography is still not optimal due to the rapid development of technology, the limited capacity of law enforcement officers, and the low digital literacy of the public. Therefore, regulatory harmonization, institutional strengthening, and increasing public legal awareness are necessary to achieve effective, adaptive, and just law enforcement.